A systematic review of metastatic lesions to the oral and maxillofacial regions among Japanese people - Seiji Asoda; Takazumi Yasui; Kenta Tanaka; Katsuhiro Onizawa; Hiromasa Kawana; Taneaki Nakagawa (Japanese Dental Science Review)
This review aimed to integrate the available data published in the literature on metastatic lesions in the oral and maxillofacial region (MOMR) and to produce an updated comprehensive analysis of its clinical characteristics, treatment, and prognosis. An electronic database search was conducted for articles concerning MOMR in Japan. The incidence and characteristics of MOMR were investigated, and the survival time was analyzed. This systematic review identified 211 studies, including 356 cases. There was a male predominance (n = 250/70.2 %) and the mean age at the diagnosis was 62.1 (range, 4–91) years old. The most common primary site was the lungs (n = 104/29.2 %). Oral metastasis sites were equally frequent in the jawbone (n = 182/51.1 %) and soft tissue (n = 174/48.9 %). Among these, the mandible and gingiva were the most common. The most common clinical presentation was a nodule (n = 317/90.3 %). The presence of metastases to other organs (P = 0.009) and uncontrolled primary lesions (P < 0.001) was associated with a shortened survival. This systematic review provides important insights into the clinical features, diagnosis, and treatment of MOMR in Japan and will assist clinicians in their appropriate management.